Pengaruh Kecerdasan Numerik Dan Konsep Diri Terhadap Motivasi Berprestasi Matematika - Zikriah Zikriah (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of this research is to analyze the effect of numerical intelligence and self-concept on mathematics achievement motivation. The method used in this research is a survey method. The research sample is selected through Multi Stage Random Sampling totaling 94 students in grade IX of private Junior High School (SMP) in Tebet subdistrict, South Jakarta. Data analysis is made by using multiple regression statistics. The results of the research are: (1) There is a directly significant effect of student's numerical intelligence on mathematics achievement motivation. (2) There is a directly significant effect on student's self-concept on mathematics achievement motivation. (3) There is a jointly significant effect of student’s numerical intelligence and student’s self-concept on mathematics achievement motivation.